Magnetic and Dielectric Property Studies in Fe- and NiFe-Based Polymer Nanocomposites - Sharma H.; Jain S.; Raj P.M.; Murali K.P.; Tummala R. (My University, 2025)
Metal–polymer composites were investigated for their microwave properties in the frequency range of 30–1000 MHz to assess their application as inductor cores and electromagnetic isolation shield structures. NiFe and Fe nanoparticles were dispersed in epoxy as nanocomposites, in different volume fractions. The permittivity, permeability, and loss tangents of the composites were measured with an impedance analyzer and correlated with the magnetic properties of the particle such as saturation magnetization and field anisotropy. Fe–epoxy showed lower magnetic permeability but improved frequency stability, compared to the NiFe–epoxy composites of the same volume loading. This is attributed to the differences in nanoparticle’s structure such as effective metal core size and particle-porosity distribution in the polymer matrix. The dielectric properties of the nanocomposites were also characterized from 30 MHz to 1000 MHz. The instabilities in the dielectric constant and loss tangent were related to the interfacial polarization relaxation of the particles and the dielectric relaxation of the surface oxides. © 2015, The Minerals, Metals & Materials Society.